Third World women and their strategies against imperialism - Busquier, Lucía María (2020)
Introduction This extract is part of an investigation in which I inquired in depth about the history and the totality of the political definitions of the Third World Women's Alliance (TWWA), an organization that perceived itself as Third World women, based in California and New York between the years 1970 and 1975. Main goal To Analyze the internationalist and anti-imperialist profile of the Third World together with its definition, taking into account the context of wars and decolonization processes that took place in the sixties and seventies in the regions of Asia, Africa and Latin America. Method and technique A qualitative analysis of written documentary sources was carried out based on the periodical Triple Jeopardy: Racism, Imperialism, Sexism promoted by TWWA. For this writing, 10 numbers were used from 16 publications. The analysis variables used were: the conception of the Third World by TWWA; The US and its imperialist policies; the anti-imperialist position of the TWWA; and what role place Third World women occupied in anti-imperialist struggles. Results The TWWA took an anti-imperialist stance, according to the TWWA, along with sexism and racism, since imperialism was one of the oppressions they faced.     [CONTINUE READING IN THE ARTICLE]